ANALISIS PADA UPAYA PENGENTASAN MASYARAKAT MISKIN MELALUI PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA DI DESA PESUCEN KABUPATEN BANYUWANGI - Ihda Madhania; Hary Priyanto; Niko Pahlevi Hentika (Nusantara Hasana Journal, 2023)
The phenomenon of poverty in Pesucen Village has received serious attention from the Pesucen Village Government through the implementation of the Village Fund Direct Cash Assistance program. The limited amount of social assistance makes people not receive it evenly and has an impact on social jealousy. Objective: To describe, analyze, and interpret the realization of the Village Fund Direct Cash Assistance program in alleviating the poor in Pesucen Village. Method: Using qualitative principles according to constructive and participatory models. Primary data from interviews, and secondary data from the results of literature studies and various regulations relevant to the substance of the research. Result: It is difficult to equalize welfare for the poor in Pesucen Village because not all poor people receive Direct Village Fund Cash Assistance. As for the reality of social jealousy due to the determination of the Village Fund Direct Cash Aid recipient community based on appointment. Conclusion: Pesucen Village Government must be guided by the principles of transparency, accountability, conditional, participatory, equal rights not discriminatory, balance of rights and obligations.